2018
DOI: 10.1186/s40411-017-0045-x
|View full text |Cite
|
Sign up to set email alerts
|

Similarity testing for role-based access control systems

Abstract: Context: Access control systems demand rigorous verification and validation approaches, otherwise, they can end up with security breaches. Finite state machines based testing has been successfully applied to RBAC systems and enabled to obtain effective test cases, but very expensive. To deal with the cost of these test suites, test prioritization techniques can be applied to improve fault detection along test execution. Recent studies have shown that similarity functions can be very efficient at prioritizing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Studies in software testing have shown that similar test cases tend to have equivalent fault detection capabilities, and no additional gain should be expected when these are simultaneously executed [27]. To mitigate these issues, similarity metrics have been used as test prioritization criteria [137,27] for access control systems [23,40] and SPLs [61,4].…”
Section: Configuration Similaritymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in software testing have shown that similar test cases tend to have equivalent fault detection capabilities, and no additional gain should be expected when these are simultaneously executed [27]. To mitigate these issues, similarity metrics have been used as test prioritization criteria [137,27] for access control systems [23,40] and SPLs [61,4].…”
Section: Configuration Similaritymentioning
confidence: 99%
“…For every missing transition, we added a self-loop transitions returning 0. This process was hand-crafted by the first author of this paper, who has former experience in modeling software systems for model-based testing [39,40] and automata learning [41]. Moreover, this process was partially automated using Bash and Python scripts that are included in our lab package.…”
Section: Splmentioning
confidence: 99%